(untitled) (Research, Society and Development, 2020)
Choosing a profession is one of the most important decisions in students’ lives. At this moment, it is essential to analyze some questions that can guide the option to be followed, considering the scenario in which the individual is inserted. The objective was to analyze the factors that motivated the choice for the Nursing course as a higher education training in a public Higher Education Institution. This is a cross-sectional, descriptive, exploratory, and qualitative study. A questionnaire with open and closed questions and a semi-structured interview script was used as data collection instruments that were applied to students in the 1st period of the nursing course. With the participation of 37 new students, there was a predominance of females and age variation between 17 and 29 years. Information related to demographic and academic data was also collected. Among the reasons that led them to choose the Nursing course, answers emerged as: ease of access to the course, care as a professional focus, family issues and identification with the profession. It is suggested to implement educational campaigns about the professions in schools, aiming to give visibility to the profession of Nurse during the choice process.